Pengembangan Sistem Manajemen Bimbingan Skripsi Mahasiswa Berbasis Web (Studi Kasus : Fakultas Ilmu Komputer Universitas Brawijaya) - Haryowinoto Rizqul Aktsar; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Undergraduate thesis writing process for college students at the Faculty of Computer Science (FILKOM) Brawijaya University is currently implemented by conducting thesis guidance directly or through the media provided by the lecturer. Several problems occur in the thesis writing process, such as the process of providing links and document access rights is done manually and inefficient which requires communication between lecturers and students. The increasing number of journals makes it difficult to find research references with the same discussion as the student thesis topic. Writing keywords experiencing errors due to human errors and keywords are also less than optimal because keywords are determined manually. In this study, a student thesis guidance manajemen system was developed which could facilitate students in conducting thesis guidance and assisting lecturers in manajemen student thesis guidance through one platform. This system utilizes several algorithms to obtain journal and keyword recommendations. These algorithms include preprocessing text, TF-IDF, and cosine similarity. The software development model used by this system is the waterfall model. Systems are tested using unit testing, validation, and compatibility. The results of validation testing conducted in all test cases give a value of 100% valid.